Susceptibility of Elasmopalpus lignosellus (Lepidoptera: Pyralidae) larvae to entomopathogenic nematodes (Rhabditida) - Berlatto Magnabosco, Maria Eduarda; Andaló, Vanessa; Janoni Carvalho, Fábio; Silva de Faria, Lucas (Revista Ceres, 2024)
The cornstalk borer, Elasmopalpus lignosellus (Lepidoptera: Pyralidae), reduces the productive potential of maize crops and is a difficult pest to manage. A management program using different methods could improve the control of E. lignosellus. Considering the potential of entomopathogenic nematodes (EPN) in reducing insect pest populations in soil, the objective of this study was to evaluate the virulence of these EPN and adjust their concentration for controlling E. lignosellus larvae under laboratory and greenhouse conditions. In the laboratory, the virulence of five EPN populations was tested; then, Heterorhabditis amazonensis MC01 was tested at four concentrations. In the greenhouse, H. amazonensis MC01 was tested at four concentrations and was applied to vessels containing maize plants and six larvae. After five days, mortality was evaluated, and means were compared using Tukey’s test (p-value < 0.05). Heterorhabditis amazonensis MC01 and S. carpocapsae All were equally virulent, reducing the larva population by more than 90%. The concentration of H. amazonensis MC01 that caused the highest mortality of larvae in the laboratory was 182 infective juveniles (IJ) larva-1. In the greenhouse, the nematode was also considered virulent to E. lignosellus since all concentrations tested caused larval mortality greater than 70%.